KESIAPAN KAWASAN MENGWI DALAM RENCANA PENGEMBANGAN KAWASAN BERORIENTASI TRANSIT DAN KETERKAITANNYA TERHADAP SDGS - I Putu Wahyu Wedanta Pucangan; Ciptadi Trimarianto (UNHI Press, 2021)
Transit-oriented areas (TOD) are related to space and place through the division of activity centers in transit-oriented areas such as ports, terminals, airports, stations by combining transportation, land use, economic, social and environmental facilities and infrastructure, transit-oriented areas, namely at Mengwi Terminal, Badung Regency. The purpose of this study is to assess the Standard TOD by ITDP in the Mengwi transit-oriented area as well as its linkage to the SDGs through qualitative methods with policy studies and descriptions as well as quantitative analysis with MCE. The results of the assessment show that the Mengwi area of Badung Regency has met the TOD standard with the Bronze category. The linkage of the Mengwi Area in the transit-oriented area development plan to the SDGs, namely in Indicator 11.2, namely and the implementation of the national urban spatial regulation strategy.